Gestations course and outcomes in patients with systemic lupus erythematosus - S J Volkova; G R Fadienko; N A Levchenko (Научно-практическая ревматология, 2003)
Objective. To study course features and gestation ourcomes in pts with systemic lupus erythematosus (SLE). To assess gestation influence on SLE course and gestation outcomes for fetus and mother. Material and methods. 27 gestation course and outcomes were followed up in 26 women with SLE admitted to Tyumen regional clinical hospital in 1995-2001 years. SLE was diagnosed according to ACR 1982 criteria. Statistical analysis was performed with MS Excel 7.0. Results. SLE exacerbated during gestation in all examined women. Autoimmune process activity increased in most pts after the end of gestation independently on its outcome and required intensive treatment methods administration. Negative perinatal SLE influence on fetus was noted even at favorite prognosis for mother. Programs of immunosuppressive therapy are administered in SLE during gestation. Conclusion. SLE presence worsens gestation course and outcomes determining high percent of medical and spontaneous abortions, exerts negative perinatal influence on fetus. Gestation appearance in pts with SLE as a rule lead to disease exacerbation as during gestation as after delivery. Presented intensive therapy programs allow to ameliorate gestation outcomes for mother and for fetus in SLE.